ByzRev 03.2021.020: Ingela Nilsson, Writer and Occasion in Twelfth-century Byzantium: the Authorial Voice of Constantine Manasses.: Cambridge – New York: Cambridge University Press 2020. - Loukaki, Marina (The Byzantine Review, 2021)
Ingela Nilsson, Writer and Occasion in Twelfth-century Byzantium: the Authorial Voice of Constantine Manasses. Cambridge – New York: Cambridge University Press 2020. X, 222 pp. – ISBN: 978-1-108-84335-5 (hardback).